Genetic Causes of Non-pathogenic Pseudomonas syringae pv. actinidiae Isolates in Kiwifruit Orchards - Li, Yue; Zhu, Qiaomei; Zhi, Taihui; Fan, Rong; Xie, Ting; Zhao, Zhibo; Long, Youhua; Li, Zhong (Frontiers in Microbiology, 2021)
Bacterial canker disease has become the largest threat to kiwifruit cultivation and production. A monomorphic subpopulation of Pseudomonas syringae pv. actinidiae biovar 3 (Psa3) is responsible for the pandemic worldwide. Diversity in pathogenicity has been found in the pandemic subpopulation and in other Psa3 subpopulations causing epidemics in China. However, the genetic bases have not yet been elucidated. In this study, 117 Psa3 isolates were identified by Psa- and Psa3-specific primers, and evaluated for pathogenicity. Three isolates G4, G40, and S2 are not pathogenic to kiwifruit and do not elicit hypersensitivity responses (HRs) in non-host Nicotiana benthamiana leaves. Two isolates, G25 and G35, exhibited attenuated HR-eliciting activity in non-host N. benthamiana, but they exhibited greatly and slightly reduced pathogenicity in host plants, respectively. The genomes of the five isolates were sequenced and compared with closely-related isolates revealed by MLVA and whole-genome typing methods. The candidate genetic loci responsible for the changes in pathogenicity and HR elicitation, were further evaluated by allele replacement experiments. We found that the three non-pathogenic isolates were formed due to the independent, identical insertion events of ISPsy36 transposon in the hrpR gene, encoding a key regulator of type III secretion system (T3SS) and type III effectors (T3Es). In the symptomatic sample from which G4 was isolated, 27% HR negative isolates were detected. In isolate G25, transposon insertion of ISPsy32 at the non-coding sequence upstream of the hrpR gene was detected, similar to a previously reported low-virulent Psa3 strain M227. In isolate G35, we detected disruptions of T3Es hopBB1-1 and hopBB1-2, which induce HR in N. benthamiana leaves revealed by Agrobacterium tumefaciens infiltration. These phenotype-changed isolates were formed at low frequencies during the course of pathogen infection in host plants, supported by the binding assay of ISPsy32 and the non-coding DNA sequences upstream of the hrpR gene, the co-isolation of the virulent isolates belonging to the same MLVA clade, and the low levels of transcription of the transposon genes. Taken together, in terms of short-term field evolution, transposon insertions in the T3SS-related genes resulted in the formation of non-pathogenic and low-virulent Psa3 isolates.